VIDEO-EEG-MONITORING IN DIAGNOSIS OF MYOCLONIC ABSENCES - M. B. Mironov; K. Yu. Mukhin; M. O. Abramov; M. Yu. Bobylova; T. M. Krasilschikova; A. S. Petrukhin (Эпилепсия и пароксизмальные состояния)
Myoclonic absences (MA) are generalised epileptic seizures, classificated as absences with special features. MA characterized by changes in the level of consciousness combined with severe bilaterally synchronous rhythmic myoclonic jerks.Objective. To study the clinical and electroencephalographic characteristics of MA.Materials and Methods. The study included 8 patients 5 to 13 years (5 female, 3 — male), in whom MA were registered during of video-EEG monitoring with the inclusion of sleep.Results. MA in wakefulness followed by stopping activity, hypomimia, the appearance of rhythmic bilateral myoclonic jerks in the muscles of the upper body and in some cases the tonic component (elevation of the arms) later joined. In 3 cases, unilateral myoclonus observed. Change in level of consciousness was able to identify if the seizure lasted for more than 5 seconds. EEG during MA in wakefulness has registered generalized bilaterally synchronous rhythmic discharges of sharp-slow wave or double / poly spike wave activity with amplitude predominance of discharges in the anterior areas. Rhythmic myoclonus coincided with a sharp wave, double-spikes, poly-spikes, complex “sharp-slow wave.” In 5 patients low amplitude fast activity (LAFA) was marked on EEG immediately before bilaterally synchronous complexes “sharp-slow wave.” In 7 cases during the sleep registered seizures with clinical and electroencephalographic characteristics of MA. It is impossible to adequately assess the level of consciousness during sleep.Conclusion. Nevertheless diagnosis absence during sleep is competent on the basis of two co-signs: changes in motor activity of the patient at the time of the EEG pattern of absences.